Curriculum Code, Arena, and Context: Curriculum and Leadership Research in Sweden. Issue 2 (3rd April 2017) - Forsberg, Eva; Nihlfors, Elisabet; Pettersson, Daniel; Skott, Pia
ABSTRACT: This article describes the development of the Swedish curriculum-theory tradition with a focus on different curriculum practices, educational message systems, arenas, and curriculum makers. Attention has been paid to different places, spaces, and times in relation to the selection, ordering, and manifestation of knowledge, norms, and values, as well as the management and organization of education. Curriculum and leadership research and changes in Swedish education are described and we introduce the comparative curriculum code as a codification of the contemporary changes in the education system and their consequences for the selection and ordering of knowledge and students.